Evolution of Carbon Nanotubes, Their Methods, And Application as Reinforcements in Polymer Nanocomposites: A Review - Daniel Rimamnya, Nyatse; Opeyemi Samson, Akanbi; Charles Bunmi, Daramola; Faith Abass, Gbemi; Joshua Olaniyan, Ajao; Akinsanmi Samson, Ige; Oluwakunle Moyofoluwa, Ogunsakin; Tajudeen Kolawole, Bello (Journal of Advanced Mechanical Engineering Applications, 2023)
The demand for increased performance in structural materials has drawn attention to the use of fiber materials as a means of reinforcement to provide structural integrity. Carbon nanotube (CNT) reinforced polymer nanocomposites have become the go-to materials due to their superior properties. CNTs possess a strength 10-100 times higher than steel yet are lighter in weight. Additionally, CNTs have a remarkable thermal stability of up to 2800°C in a vacuum, and an electrical conductivity of 103 S/cm. It also has an electric-current-carrying capacity 1000 times higher than other materials and a thermal conductivity of around 1900 W m-1 K-1, which is almost double that of diamond. This article explores the potential of Carbon Nanotubes (CNTs) to reinforce structural composite materials, improve sensing, and enhance responsiveness. It also examines its structure and classification as single and multi-walled, its synthesis, including laser ablation methods, arc discharge methods, chemical vapor deposition methods, and spray pyrolysis. Additionally, it discusses the applications, structural benefits, and challenges of composite materials.